Perceptions of social media harms and potential management strategies: Vaping case study - Jancey, Jonine; Crawford, Gemma; Bowman, Elizabeth; Wolf, Katharina; Leaver, Tama; Bialous, Stella; McCausland, Kahlia (BioMed Central, 2024)
Background The social media landscape is now ubiquitous in people’s everyday lives. It is a space where culture, politics, economics and sociological and public health discourses occur. There is mounting evidence that e-cigarette products are being promoted and advertised on social media, a media platform particularly popular with young people. Our research aimed to understand industry professionals’ perceptions of social media harms and potential management strategies using vaping as a case study.